1984
DOI: 10.1007/bf00818255
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of acto-S1 interaction as a guide to a model for the crossbridge cycle

Abstract: Recent experiments on the kinetics of the interaction between myosin subfragment 1 (S1) and F-actin in solution are summarized. It is concluded that, at every step of the ATPase cycle, the association between the two proteins takes place in two stages. The equilibrium constant of the second step and thus the affinity of S1 for actin changes from step to step during the enzymatic reaction. It is proposed that the transient kinetic evidence can be interpreted in terms of two different classes of contraction mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

22
125
2

Year Published

1987
1987
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 163 publications
(149 citation statements)
references
References 23 publications
22
125
2
Order By: Relevance
“…With the sinusoidal analysis method, we characterized the cross-bridge scheme in rabbit psoas fibres (Kawai and Halvorson 1991), soleus slow twitch fibres (Wang and Kawai 1997), ferret cardiac fibres , porcine cardiac fibres , bovine cardiac fibres , and other fast twitch skeletal muscle fibres from the rabbit (Galler et al 2005). The above Scheme 1 is consistent to those deduced from solution studies (Taylor 1979;Geeves et al 1984) of isolated and reconstituted contractile proteins, except that in solution studies the strongly bound AM*DP state has not been identified, the Pi release step (step 5) is practically irreversible (Taylor 1979), and the ATP isomerization step (step 2) is irreversible (k −2 = 0) in the interaction of myosin subfragment 1 and MgATP (Bagshaw and Trentham 1974). The irreversibility (extremely large K) means that the free energy reduction is large because of the relationship: ΔG° = −RT ln K, which means that perhaps half of the ATP hydrolysis energy is dissipated at step 2 and another half at step 5 in the case of solution studies.…”
Section: Methods Of Studying Cross-bridge Kineticssupporting
confidence: 67%
“…With the sinusoidal analysis method, we characterized the cross-bridge scheme in rabbit psoas fibres (Kawai and Halvorson 1991), soleus slow twitch fibres (Wang and Kawai 1997), ferret cardiac fibres , porcine cardiac fibres , bovine cardiac fibres , and other fast twitch skeletal muscle fibres from the rabbit (Galler et al 2005). The above Scheme 1 is consistent to those deduced from solution studies (Taylor 1979;Geeves et al 1984) of isolated and reconstituted contractile proteins, except that in solution studies the strongly bound AM*DP state has not been identified, the Pi release step (step 5) is practically irreversible (Taylor 1979), and the ATP isomerization step (step 2) is irreversible (k −2 = 0) in the interaction of myosin subfragment 1 and MgATP (Bagshaw and Trentham 1974). The irreversibility (extremely large K) means that the free energy reduction is large because of the relationship: ΔG° = −RT ln K, which means that perhaps half of the ATP hydrolysis energy is dissipated at step 2 and another half at step 5 in the case of solution studies.…”
Section: Methods Of Studying Cross-bridge Kineticssupporting
confidence: 67%
“…In each cycle, myosin hydrolyzes a single ATP molecule and couples this chemical reaction to the physical state transition between the weak and strong actin-binding states (11 and 12). The weakto-strong actin-binding transition has been thought to play a key role in the force-generation (12). However, when and how the force is generated remains controversial (7 and 13).…”
mentioning
confidence: 99%
“…1). Although skeletal muscle actomyosin II binds ADP weakly (K d Ͼ 100 M) in a rapid equilibrium (4), smooth muscle myosin (5) and some nonmuscle actomyosin isoforms (6 -10) bind ADP with high (K d Ͻ 10 M) affinities. Several actomyosins with high ADP binding affinities display an ADP-induced rotation of the light chain binding domain (11,12) and are likely to populate multiple actomyosin-ADP states (5)(6)(7).…”
mentioning
confidence: 99%